Impact of the location of retail outlets on the formation of household supply flows in the autonomous district of Lome - Djossou, Kodjo; Dandonougbo, Iléri; Lyonnet, Barbara; Abbad, Hicham (Edelweiss Applied Science and Technology, 2026)
Household shopping trips are a key component of urban logistics. They enable households to be supplied with goods by connecting points of sale and homes. However, they are influenced by several factors, including the location of shops. This study aims to characterize the shopping trips of the population of the Autonomous District of Greater Lomé (DAGL) by examining the effect of retail outlet location on household supply flows. A mixed methodological approach, based on qualitative and quantitative surveys of 1,065 individuals, was adopted. The results reveal that 72% of households prefer local retail outlets, compared to 13% who frequent distant retail outlets. Motorcycles and walking are more commonly used for local travel, while motorcycles and city taxis dominate for longer trips. Furthermore, local retail outlets are visited an average of 6.3 times per month and account for an average monthly travel budget per household of 2,323 CFA francs, while visits to distant retail outlets are lower (3.5 times per month) with an average monthly budget per household of 5,042 CFA francs. These results provide a decision-making tool for urban logistics and urban planning stakeholders.